Use of ion-assisted sputtering technique for producing photocatalytic titanium dioxide thin films: Influence of thermal treatments on structural and activity properties based on the decomposition of stearic acid. (November 2018) - Vishnyakov, V.; Kelly, P.J.; Humblot, J.; Kriek, R.J.; Allen, N.S.; Mahdjoub, N.
Abstract: Titanium dioxide thin films were deposited by the reactive ion-assisted sputtering method from titanium targets at various partial pressures and deposition parameters. The films were deposited onto substrates at temperatures ranging from room-temperature conditions to 722 K. A selection of thin films was post-deposited annealed at temperatures up to 972 K for 10 min and characterized by micro-Raman spectroscopy and scanning electron microscopy (SEM) and subsequently analysed to assess their photocatalytic activity. Micro-Raman characterization revealed that the as-deposited films had either predominant amorphous, rutile-like structures, anatase-like structures or anatase-rutile mixed structures. The thin films deposited with a high substrate temperature and with energy assistance from the ion source tended to be amorphous, while films deposited on a hot substrate without ion energy assistance tended to have a mixed crystalline phase. On subsequent annealing the amorphous films changed to a rutile structure at temperatures above 672 K, while mixed anatase-rutile films changed to predominant rutile structures only after thermal treatments above 872 K. Thus, this study has revealed an astonishing persistence of the anatase-rutile mixed phase at very high temperatures and showed the possible existence of a key transition temperature at 672 K, where it was possible to see a transformation from amorphous or mixed phase to a rutile or dominant rutile mixed phase. Photocatalytic tests were undertaken by using a novel method consisting of observing the degradation of a film of stearic acid by the thin films under artificial UV radiation. Of the films investigated those with anatase-rutile mixed phases showed the greatest photoactivity. This work was essential in the understanding of the correlation between growth deposition conditions, phase transitions and photocatalytic activity. This set of experiments demonstrated that titania made under a highly oxidizing atmosphere, with no temperature applied on the substrate during fabrication and using an ion sputtering method, is a useful and valuable novel method for creating active TiO2 thin films. Highlights: Titanium dioxide thin films were deposited by the reactive ion-assisted sputtering method from titanium targets at various parameters. The films were deposited onto substrates at temperatures ranging from room-temperature conditions to 722 K. Films were post-deposited annealed at temperatures up to 972 K for 10 min and analysed to assess their photocatalytic activity. Micro-Raman characterization revealed that the as-deposited films had either amorphous, rutile-like, anatase-like or anatase-rutile structures. Photocatalytic tests demonstrated that titania made by an ion sputtering method, is a useful and valuable novel method for creating active TiO2 thin films.